Spontaneous pneumothorax in an allogeneic cell transplant recipient with invasive pulmonary aspergillosis and antecedent RSV pneumonitis - Liang Piu Koh; Michelle L Poon; John K Tam; Lynette Teo; Li Yang Hsu (Mediterranean Journal of Hematology and Infectious Diseases)
We report a case of invasive pulmonary aspergillosis (IPA) following respiratory syncytial virus infection in an allogeneic hematopoietic stem cell transplant (HCT) recipient with chronic graft-versus-host disease. Delayed diagnosis of IPA resulted in the development of a pneumothorax, a rare consequence of fungal pneumonia. Respiratory virus infections are often harbingers of other infective organisms in HSCT recipients, and more aggressive diagnostic investigations such as computed tomography scans of the thorax and bronchoscopy with bronchoalveolar lavage should be considered early in any HCT patient presenting with respiratory virus pneumonia, particularly if atypical features are present or delayed recovery occurs.